Life cycle assessment and mechanical strength of cement composites with conventional, and recycled fine aggregate - Sk. Rakibul Islam; Sanjima Nabila Majumder; Rupak Mutsuddy (Sustainable Structures)
Generally, sand as a filler material in the concrete composite is mined from the riverbed, which is the primary source of the entailed fine aggregate to keep pace with the emergent demand for concrete production. Unbridled sand extraction from the riverbed and the river bank has detrimental impacts on the environment and river geomorphology. On the other hand, construction and demolition sites generate a significant amount of solid waste, which contains fine aggregate. This study aims to explore the applicability of recycled fine aggregate (RFA) in comparison to coarse sand and fine sand in cement composites, considering their compressive strength, financial aspect, and environmental sustainability by means of Life Cycle Assessment (LCA). Hence, 12 (twelve) different combinations of the aforementioned fine aggregates were taken into consideration to determine the extent of using RFA as a replacement for conventional fine aggregates, signifying the motivation of the study. In this study, the crushing strength of cement mortars at different curing ages was compared. At 28 days, mortar with 100% coarse sand showed 25% higher, and mortar with 100% fine sand showed 67% lower compressive strength than the mortar with 100% RFA. The mix combination of 25% RFA and 75% coarse sand produced the cement mortar with a maximum compressive strength of 48.25 MPa. From LCA, subsuming the waste product (RFA) into cement composite exhibited the lowest environmental impact, in contrast to those made with natural sand. Considering the physical properties of fine aggregates, and the crushing strength of mortar along with environmental and economic aspects, cement mortar with RFA can be an environmentally sustainable option and an approach to reduce construction waste and expenses.